Rereading Freyre against Freyre: Counterhegemonic apropriation of hybridity in the South Atlantic - Melo, Alfredo Cesar (Via Atlântica, 2014)
Gilberto Freyre's role as supporter of the Portuguese New State is widely documented and examined. Freyre employ's a rethoric of hybridity to legitimize the portuguese colonial enterprise. In this article, I examine how cape verdian intellectuals instrumentalized Freyre's work in order to both rebuke his lusotropicalist stands and imagine other possible ideas of hybridity.